When Fashion Meets Social Commitment: The Case of Ara Lumiere. Issue 3 (2nd September 2018) - Noris, Alice; Kalbaska, Nadzeya; Cantoni, Lorenzo
Abstract: Ara Lumiere is a young fashion luxury brand founded by the Indian businesswoman and philanthropist Kulsum Shadab Wahab, combining her passion for fashion with social commitment within the Indian community. The brand produces unique handmade headgears, pins and foulards, all hand crafted by women that have been assaulted in acid attacks. The aim of this short review is to provide through the Ara Lumiere case a framework to better understand which connections and implications can occur among luxury fashion, social commitment, and sustainability and to understand if Social Responsibility can become an integral part of a luxury fashion brand and the formula for its success.